Clinical study of morphological changes in the arterial blood supply of the testicle in children - V. M. Baibakov (Клінічна хірургія)
Objective. Studying of clinical and morphological changes in the arterial blood supply of testicle in its surgical diseases and improvement of the surgical treatment tactics.